PHARMACOLOGICAL ACTIVITY OF ULVA LACTUCA POLYPHENOLS FRACTION: HEPATOPROTECTIVE AND ANTIOXIDANT ACTIVITIES AGAINST PARACETAMOL-INDUCED LIVER DAMAGE IN RATS - RAVINDRAN NT,; MOHAMED SADIQ A, (Asian Journal of Pharmaceutical and Clinical Research, 2019)
Objective: The objective of this study was to assess the activity Ulva lactuca polyphenols fraction in protecting the liver damage induced by high dose of paracetamol. Methods: This study was performed using Wistar albino rats divided into six groups. Group 1 was the normal group. Groups 2, 3, 4, 5, and 6 received paracetamol (2 g/kg) for 7 days. In addition to paracetamol, Groups 3, 4, 5, and 6 received silymarin (100 mg/kg), U. lactuca polyphenols fraction at the doses of 50, 100, and 200 mg/kg, respectively, for 7 days. On the 8th day, serum and liver samples were collected from the animals and the hepatoprotective and antioxidant activities were assessed by studying the levels of liver marker enzymes, bilirubin, protein, reduced glutathione, and antioxidant enzymes. Results: U. lactuca polyphenols fraction, at the tested doses, restored the levels of all serum markers and enzymes (aspartate aminotransferase, alanine aminotransferase, alkaline phosphatase, lactate dehydrogenase, γ-glutamyl transferase, total bilirubin, total protein, cholesterol, triglycerides, and reduced glutathione) and liver homogenate markers (reduced glutathione, superoxide dismutase, catalase, and glutathione peroxidase) significantly, in dose-dependent manner. Conclusion: This study suggests that U. lactuca polyphenols fraction has a hepatoprotective effect against paracetamol-induced liver damage and possesses antioxidant activities.